The difficulties of students in beginning college physics in the University of the Philippines - Alarilla, Luis M. 1912- (Manila University of the Philippines Manila, 1941)
This study sought to find the means which would enhance greater efficiency in the teaching of College Physics. The knowledge of the difficulties of the students on the part of the teacher would put them in a better position to analyze and properly adjust the learning process.
Typewritten
Vita
Thesis (M.A.)--University of the Philippines, Manila
Keywords: Physics -- Study and teaching